Dataset associated with "Emissions and radiative impacts of sub-10 nm particles from biofuel and fossil fuel cookstoves" - Jathar, Shantanu H.; Sharma, Naman; Bilsback, Kelsey R.; Pierce, Jeffrey R.; Vanhanen, Joonas; Gordon, Timothy D.; Volckens, John (Colorado State University. Libraries, 2020)
Combustion sources have been shown to directly emit particles smaller than 10 nm. The emission of 1-3 nm particles from biofuel or fossil-fuel cookstoves has not been studied previously, nor have the radiative impacts of these emissions been investigated. In this work, emissions (number of particles) were measured during a water boiling test performed on five different cookstoves (three-stone fire, rocket elbow, gasifier, charcoal, and liquified petroleum gas [LPG]) for particle diameters between ~1 and ~1000 nm. We found significant emissions of particles smaller than 10 nm for all cookstoves (>5×1015 # kg-fuel-1). Furthermore, cleaner (e.g., LPG) cookstoves emitted a larger fraction of sub-10 nm particles (relative to the total particle counts) than traditional cookstoves (e.g., three-stone fire). Simulations performed with the global chemical transport model GEOS-Chem-TOMAS that were informed by emissions data from this work suggested that sub-10 nm particles were unlikely to significantly influence number concentrations of particles with diameters larger than 80 nm that can serve as cloud condensation nuclei (CCN) (<0.3%, globally averaged) or alter the cloud-albedo indirect effect (absolute value <0.005 W m-2, globally averaged). The largest, but still relatively minor, localized changes in CCN-relevant concentrations (<10%) and the cloud-albedo indirect effect (absolute value <0.5 W m-2) were found in large biofuel combustion source regions (e.g., Brazil, Tanzania, Southeast Asia) and in the Southern Ocean. Enhanced coagulation-related losses of these sub-10 nm particles at sub-grid scales will tend to further reduce their impact on particle number concentrations and the aerosol indirect effect, although they might still be of relevance for human health.
The dataset includes (i) measurements of particle emissions from several different cookstoves performed during a water boiling test and (ii) atmospheric concentrations and impacts from simulations performed with a global chemical transport model. These data need to be archived alongside an accepted manuscript in Aerosol Science and Technology. The cookstove measurements were performed in Fall of 2018 and Spring of 2020. The model simulations were performed in Fall of 2019.
Department of Mechanical Engineering
Department of Atmospheric Science
Keywords: nanocluster aerosols; cookstoves; chemical transport modeling; aerosol indirect effect